Publicidade autorreferencial do diário gaúcho: encenações do produto midiático e do leitor - Depexe, Sandra Dalcul (2010)
In this work the focus given to the printed newspaper goes beyond the function institutionalized in the social construction of reports and is focused on the notion product media to be "sold" the advertising market. The attention is back to ads that reference the vehicle of communication in which being published as self-referential ads. The main goal is to investigate the construction of newspaper in self-referential ads from daily Diário Gaúcho, owned by RBS - Rede Brasil Sul to systematize the variables present in the contracts of communication advertisements in order to find formations that indicate the mise en scène of the media product and the popular reader. Contribution of concept of articulation (HALL, 2003) aligned with cultural studies, suggests that the text and context of advertising fall within production journalism as a self-reference: the media instance strain promise and product in the same space of movement, marked by certain cultural matrices (SUNKEL, 1985). Adopts the notion of communication contract (CHARAUDEAU, 2006) as a theoretical methodological analysis of the corpus consisted of nineteen ads published in different editions of the newspaper Diário Gaúcho, between 2008 and 2009. It appears that the link between advertising and the media context fuses the joints themselves the product of the media with his audience. For Diário Gaúcho is remarkable transposition of concepts adopted in its editorial announcements: strengthens precepts of popular journalism, directed to an audience without the habit of reading. The newspaper is mise en scène as a friend of the reader, there is thus erasing the characteristics of newspaper as media product. The reader is mise en scène in two perspectives: one that celebrates the warmth, joy, color and traditions, and another that refers to position of subordination and helplessness experienced by the working classes. Advertising self-referential Diário Gaúcho builds the newspaper by subjective and emotional bias in the manner cultural matrix of symbolic-dramatic, of overlapping the contract to identification with the reader.